Analytical review and the analysis of educational programs with CMSE content - Зупанчич, Борут; Сениченков, Юрий Борисович; Мушич, Гаспер (Computer Tools in Education, 2017)
The paper deals with the outcomes of a working package in the ERASMUS+ project entitled InMotion in which European partners should help to establish improved programs with modelling and simulation content in Malaysia and Russian Federation. By the aid of a survey the analytical review and the analysis of educational programs with computer modelling and simulation engineering content was performed. The survey was sent to partner universities and worldwide. The answers were analysed for bachelor, master and PhD programs with regard to the basic information (duration, contact hours and individual work, final work, practical orientation of the study and elective courses), with regard to curricula and competencies. The final part is devoted to the investigation whether there are some bachelor, master and PhD programs that are completely in the area of modelling and simulation. We were able to find only one example of such institution in US.